Source-drain electrical conduction and radiation detection in graphene-based field effect transistor (GFET). (2nd February 2022) - Torrisi, L.; Salvato, G.; Cutroneo, M.; Librizzi, F.; Torrisi, A.; Silipigni, L.
Abstract: Electrical measurements on a graphene field effect transistor (GFET) are presented and discussed for its characterization in vacuum and in air. In this last environment three low output power continuous wave (CW) led lasers and a UV lamp have been used to study the illumination effects at wavelengths from the near infrared (NIR) to red, green up to near UV. In air the device is sensitive to visible and UV radiation. The visible light produces charge carriers increasing the source-drain current. Instead, the UV radiation induces the graphene oxidation decreasing the source-drain current in a permanent way. Small temperature increments, up to about 55 ∘ C, increase the electrical conduction. Larger temperatures and prolonged heating in air generate oxidation, decreasing the source-drain current. As far as the NIR radiation is concerned, no effect is observed. Therefore, these preliminary investigations indicate that the device can be employed as visible and UV radiation detector.